2013
DOI: 10.5005/jp-journals-10026-1104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Compressive Strength for a Combination of Glass Ionomer Cement and Antibiotics

Abstract: Aims and objectives: Since atraumatic restorative treatment (ART) involves removal of carious lesions with manual instruments, there are more chances of residual bacteria under the glass ionomer restoration which might lead to secondary caries. Hence improving the antibacterial effect of glass ionomer cement helps in achieving better success rate. This study aimed to evaluate the compressive strength of glass ionomer cement containing different antibiotics. Materials and methods:Conventional restorative glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The recorded values of compressive strength (MPa) for both control and experimental groups were less than that reported in literature. [ 4 16 35 ] This could be due to the difference in the method of casting the specimens and the mechanical testing procedure. Since the detection of internal defects was beyond the confines of our study, their effect on the compressive strength of the material cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The recorded values of compressive strength (MPa) for both control and experimental groups were less than that reported in literature. [ 4 16 35 ] This could be due to the difference in the method of casting the specimens and the mechanical testing procedure. Since the detection of internal defects was beyond the confines of our study, their effect on the compressive strength of the material cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Compressive strength is an important property of tooth restorative materials, which can help protect materials from masticatory forces. [34][35][36] Compressive strengths can vary depending on the mixing and placement methods as well as the conditions maintained during measurement. Bresciani E et al found that compressive strength of marketed ART (Bioglass R) was 99 MPa.…”
Section: Compressive Strengthmentioning
confidence: 99%